Lentinan Supplementation Protects the Gut–Liver Axis and Prevents Steatohepatitis: The Role of Gut Microbiota Involved - Yang, Xiaoying; Zheng, Mingxuan; Zhou, Menglu; Zhou, Limian; Ge, Xing; Pang, Ning; Li, Hongchun; Li, Xiangyang; Li, Mengdi; Zhang, Jun; Huang, Xu-Feng; Zheng, Kuiyang; et al. (Frontiers in Nutrition, 2022)
The microbiota–gut–liver axis has emerged as an important player in developing nonalcoholic steatohepatitis (NASH), a type of nonalcoholic fatty liver disease (NAFLD). Higher mushroom intake is negatively associated with the prevalence of NAFLD. This study examined whether lentinan, an active ingredient in mushrooms, could improve NAFLD and gut microbiota dysbiosis in NAFLD mice induced by a high-fat (HF) diet. Dietary lentinan supplementation for 15 weeks significantly improved gut microbiota dysbiosis in HF mice, evidenced by increased the abundance of phylum Actinobacteria and decreased phylum Proteobacteria and Epsilonbacteraeota. Moreover, lentinan improved intestinal barrier integrity and characterized by enhancing intestinal tight junction proteins, restoring intestinal redox balance, and reducing serum lipopolysaccharide (LPS). In the liver, lentinan attenuated HF diet-induced steatohepatitis, alteration of inflammation–insulin (NFκB-PTP1B-Akt-GSK3β) signaling molecules, and dysregulation of metabolism and immune response genes. Importantly, the antihepatic inflammation effects of lentinan were associated with improved gut microbiota dysbiosis in the treated animals, since the Spearman's correlation analysis showed that hepatic LPS-binding protein and receptor (Lbp and Tlr4) and pro- and antiinflammatory cytokine expression were significantly correlated with the abundance of gut microbiota of phylum Proteobacteria, Epsilonbacteraeota and Actinobacteria. Therefore, lentinan supplementation may be used to mitigate NAFLD by modulating the microbiota–gut–liver axis.